Suartėjimas: koegzistencinės analizės patirtis - Tatiana Shchyttsova (Problemos, 2014)
The essay carries out the primary phenomenological explication of rapprochement (drawing nearer) as a fundamental mode of Being-with-one-another. Proceeding from the existential interpretation of space given in Heidegger's Being and Time the author shows that Heidegger's clarification concentrates exclusively on the relation to an ready-to-hand equipment and ignores the question of how nearness and distance in the relation to the Other are determined while the very approach chosen by Heidegger for such clarification turns to be unacceptable for this new question. In this connection the paper is aimed, first of all, at letting the phenomenon show itself. It is achieved due to the phenomenological description of the experience of death of the near one. This experience proves the fact of nearness in its immediate evidence and in actu. Explication of the phenomenon of drawing nearer allows, finally, to introduce several basic characteristics which distinguish the world of nearness from the world of publicity.